Inclusion: construction and adaptation of chemistry laboratory materials for a student with cerebral palsy - Lucia Teixeira Guerra de Mendonça, Maria; Petinatti da Cruz, Rosana; M. Manhães, Marília; M. V. Santos, Alba; Almeida Vieira, Flavia (Seven Editora, 2023)
The objective of the work was to build and/or adapt laboratory materials, to be used in the experimental classes of General Chemistry I, for a student who presented cerebral palsy.  The methodology consisted in the observation of the commitment of the student and later the elaboration of specific material for the student to be able to execute the experimental class.  The results were quite significant, with the student inserted in the class and executing all the proposed tasks. It was concluded that even with all the commitment that the student presented, there was the insertion of the student in the experimental subject and consequently to the class, to the course and also to the world. DOI: https://doi.org/10.56238/tfisdwv1-033